Design, Control and Testing of a Modular Multilevel Converter with a Single Cell per Arm in Grid-Forming and Grid-Following Operations for Scaled-Down Experimental Platforms - Jaume Girona-Badia; Oriol Gomis-Bellmunt; Tomàs Lledó-Ponsati; Macià Capó-Lliteras; Carlos Collados-Rodriguez; Nicolaos Antonio Cutululis; Oscar Saborío-Romano; Daniel Montesinos-Miracle; Marc Pagès; Daniel Heredero-Peris; Eduardo Prieto-Araujo (Energies, 2022)
Modular multilevel converters (MMC) can be used in several applications, especially (but not only) in high-voltage direct current (HVDC) and STATCOM. In order to develop experimental scaled-down test benches for lab validation, several projects have developed MMCs with a limited number of cells, but they need to use pulse width modulation (PWM) techniques to achieve acceptable power quality (because nearest level modulation (NLM), common in HVDC applications with hundreds of levels, cannot achieve sufficient power quality unless the number of cells is high enough). The present paper proposes a new concept which is based on designing arms with a single cell. This allows to have the simplest possible converter that maintains the structure of an MMC. While all the inner controllers of large-scale HVDC MMCs are included, the only remarkable difference is that PWM is used and NLM cannot be implemented. As this is also a limitation for other low voltage MMC, the proposed concept is suggested for scaled-down low voltage applications. The paper includes the design and construction of the converter, the definition and implementation of the converter controllers, and the converter testing, with detailed dynamic simulations and an experimental setup.